Portable Gait Analysis System with an Integration of Kinect sensor and Inertial Measurement Units. Issue 1 (September 2020) - Saravanan, Pratima; Yao, Jiyun; Menold, Jessica
Clinical gait analysis is used for diagnosing, assessing, and for monitoring a patient by analyzing their kinetics, kinematics and electromyography while walking. Traditionally, gait analysis is performed in a formal laboratory environment making use of several high-resolution cameras, either video or infrared. The subject is asked to walk on a force platform or a treadmill with several markers attached to their body, allowing cameras to capture the joint coordinates across time. The space required for such a laboratory is non-trivial and often the associated costs of such an experimental setup is prohibitively expensive. The current work aims to investigate the coupled use of a Microsoft Kinect and Inertial Measurement Units as a portable and cost-efficient gait analysis system. Past studies on assessing gait using either Kinect or Inertial Measurement Units concluded that they achieve medium reliability individually due to some drawbacks related to each sensor. In this study, we propose that a combined system is efficient in detecting different phases of human gait, and the combination of sensors complement each other by overcoming the individual sensor drawbacks. Preliminary findings indicate that the IMU sensors are efficient in providing gait kinematics such as step length, stride length, velocity, cadence, etc., whereas the Kinect sensor helps in studying the gait asymmetries by comparing the right and left joint, such as hips, knees, and ankle.